Impact of Human Immunodeficiency Virus Type 1 Minority Variants on the Virus Response to a Rilpivirine-Based First-line Regimen. (8th January 2018) - Raymond, Stéphanie; Nicot, Florence; Pallier, Coralie; Bellecave, Pantxika; Maillard, Anne; Trabaud, Mary Anne; Morand-Joubert, Laurence; Rodallec, Audrey; Amiel, Corinne; Mourez, Thomas; Bocket, Laurence; Beby-Defaux, Agnès; et al.
Abstract : Next-generation sequencing retrospectively identified rilpivirine-resistant variants with a 1% threshold in 8.8% and 5.7% of 489 treatment-naive patients according to the ANRS and Stanford algorithms, respectively. Minority resistant variants had no impact on the virological response to a rilpivirine-based regimen. Abstract: Background: Minority resistant variants of human immunodeficiency virus type 1 (HIV-1) could influence the virological response to treatment based on nonnucleoside reverse transcriptase inhibitors (NNRTIs). Data on minority rilpivirine-resistant variants are scarce. This study used next-generation sequencing (NGS) to identify patients harboring minority resistant variants to nucleos(t)ide reverse transcriptase inhibitors and NNRTIs and to assess their influence on the virological response (VR). Methods: All the subjects, 541 HIV-1–infected patients started a first-line regimen containing rilpivirine. VR was defined as a HIV-1 RNA load <50 copies/mL at month 6 with continued suppression at month 12. NGS was performed at baseline (retrospectively) on the 454 GS-FLX platform (Roche). Results: NGS revealed resistance-associated mutations accounting for 1% to <5% of variants in 17.2% of samples, for 5%–20% in 5.7% of samples, and for >20% in 29% of samples. We identified 43 (8.8%) and 36 (7.4%) patients who harbored rilpivirine-resistant variants with a 1% sensitivity threshold according to the French National Agency for Research on AIDS and Viral Hepatitis and Stanford algorithms, respectively. The VR was 96.9% at month 12. Detection of minority rilpivirine resistant variants was not associated with virological failure (VF). Multivariate analysis indicated that VF at month 12 was associated with a CD4 count <250 cells/µL at baseline, a slower decrease in viral load at month 3, and rilpivirine resistance at baseline using the Stanford algorithm with a 20% threshold. Conclusions: Minority resistant variants had no impact on the VR of treatment-naive patients to a rilpivirine-based regimen.